2012
DOI: 10.1007/s12178-011-9109-4
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances following anterior cruciate ligament reconstruction: rehabilitation perspectives

Abstract: Injuries to the anterior cruciate ligament are common. Surgical reconstruction is more prevalent than ever. This review article discusses treatment of the patient following surgical reconstruction of the anterior cruciate ligament. Various phases of rehabilitation are discussed with emphasis on early return of passive motion, early weight bearing, bracing, kinetic chain exercises, neuromuscular electrical stimulation and accelerated rehabilitation. Although evidence exists for the treatment of the surgically r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 109 publications
(97 reference statements)
0
28
0
2
Order By: Relevance
“…Manske et al 30 in a systemic review of the latest evidence regarding ACL rehabilitation, incorporated a phase-wise rehabilitation protocol starting from the immediate rehabilitation to more than 6 months postoperative rehabilitation and home-based rehabilitation as compared to the supervised therapy by physical therapist. The studies in the above systemic review suggested that home-based therapy may produce similar outcomes as clinicalbased programs.…”
Section: Discussionmentioning
confidence: 99%
“…Manske et al 30 in a systemic review of the latest evidence regarding ACL rehabilitation, incorporated a phase-wise rehabilitation protocol starting from the immediate rehabilitation to more than 6 months postoperative rehabilitation and home-based rehabilitation as compared to the supervised therapy by physical therapist. The studies in the above systemic review suggested that home-based therapy may produce similar outcomes as clinicalbased programs.…”
Section: Discussionmentioning
confidence: 99%
“…Do najbardziej spektakularnych następstw urazów stawu kolanowego zalicza się uszkodzenia w obrębie aparatu więzadło-wego, zwłaszcza więzadła krzyżowego przedniego (ACL). Całkowite zerwanie ACL w zdecydowanej większości przypadków wymaga specjalistycznego leczenia operacyjnego (rekonstrukcji ACL) [6][7][8][9][10][11][12][13][14][15][16][17].…”
Section: Wstępunclassified
“…By the end of the first week (visit 4), he continued to report pain along patellar incision site with extension activities and weight bearing activities. Due to ACL autograft BTB reconstruction, it is expected that patient would have more patellofemoral complications due to scarring of these areas [27]. During visit 4, treatment was modified to include moist hot pack to reduce pain, increase circulation and improved tissue extensibility as a preparatory technique for manual techniques [28].…”
Section: Post-treatment Knee Flexionmentioning
confidence: 99%